TINDAK TUTUR ILOKUSI SYAIR LAGU PADA ALBUM MEMBANGUN DAN MENGHANCURKAN KARYA FEAST - Syam, Andika Idul; Johar Amir; Rizki Herdiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe: the functions of illocutionary speech acts found in the song lyrics of the album Membangun dan Menghancurkan by Feast. This study employs a descriptive qualitative approach. The data consist of utterances or linguistic units containing illocutionary speech acts in the song lyrics “O, Tuan,” “Nina,” and “Tarot.” The data source of this study is the text of the song lyrics in the album Membangun dan Menghancurkan by Feast. Data collection was conducted through documentation methods, involving the steps of observing, note-taking, and classifying the data according to the research focus. The research instrument is the researcher themselves, supported by a data classification sheet based on John R. Searle’s theory of illocutionary speech acts. The data analysis technique uses the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results show that there are five types of illocutionary speech acts: representatives, directives, commissives, expressives, and declaratives, which function to convey attitudes, express commitments, make requests, make announcements, and present the speaker’s viewpoints.